Effect of rare earth cerium on the impact toughness, corrosion and wear resistance of CrNiMnMo alloyed lining steel. Issue 2 (19th February 2020) - Du, X.; Lei, X.; Wang, J.; Zhao, Q.; Ge, H.
Abstract: The effects of the addition of rare earth cerium on the impact corrosion and wear resistance of CrNiMnMo alloyed lining steel were studied using metallurgical microscopy, scanning electron microscope, x‐ray powder diffraction, a hardness tester, an impact tester, and an impact corrosion abrasion tester. The properties of CrNiMnMo alloyed lining steel with the addition of cerium were compared with that of CrNiMnMo steel without the addition of cerium after being heat treated by same processes. The results show that CrNiMnMo alloyed lining steel with the addition of rare earth cerium consisted of lath martensite with a low residual austenite phase after being quenched and tempered. The lath of the martensite was fine and uniform. The impact toughness and the corrosion resistance of the steel lining board improved greatly with the addition of cerium and the impact toughness increased by 22 % with the fracture mode of being ductile. The CrNiMnMo alloyed lining steel with cerium showed the highest resistance to impact corrosion abrasion compared with the alloy without cerium. Abstract : This paper is devoted to improving the properties of CrNiMnMo alloy liner steels by adding rare earth element. The impact toughness and corrosion resistance were improved significantly with adding trace rare earth cerium. Especially, the impact toughness increases by 22 %. This liner steel shows better properties and longer life than that without rare earth.